Deteksi Pelanggaran pada Zebra Cross dengan Water Spray dan Buzzer berbasis IoT - Firdaus, Dina Uzlifatul; Christanto, Febrian Wahyu (UIN Sunan Kalijaga Yogyakarta, 2024)
A zebra crossing is a road marking indicating a crossing path for pedestrians. Zebra crossings are directly used to signal drivers to stop at the line boundaries. Because the zebra crossing functions as a crossing area, pedestrians and motorized vehicle drivers must understand and obey existing traffic signs. According to data from the WHO (World Health Organization), 270,000 pedestrians die every year or around 22% of all victims who die due to road accidents. An ESP32-Cam microcontroller, an E18-D80NK Infrared Proximity Sensor, water spray and buzzer approaches, and the prototype development method were used to design a system for detecting crossing violations at zebra crossings to address this issue. The Infrared Proximity sensor will automatically detect when a crossing violation occurs, then the water spray will spray water, and the buzzer will make a sound as a warning sign to obey traffic. ESP32-Cam functions as an image capturer if a crossing violation has occurred and is automatically sent to the Telegram Bot. The confusion matrix test tested the research results with an accuracy value of 83.33%, a precision value of 83.33%, and a recall value of 88.23%.